Outcomes of Dementia Among Dialysis Patients: A Nationwide Population-Based Study in Taiwan - Shen, Hsiu-Chu; Chien, Chih-Chiang; Weng, Shih-Feng; Wang, Jhi-Joung; Kuo, Jinn-Rung; Lin, Kao-Chang (Journal of Neurology and Epidemiology, 2014)
Background: High prevalence of cognitive impairment or dementia is associated with end-stage renal disease (ESRD). The risk for dementia and its prognostic significance remain unclear. This study aimed to determine the prevalence, correlations and outcomes of dementia in chronic ESRD dialysis patients. Methods: Using Taiwan National Health Insurance Research Database (NHIRD), we analyzed ESRD patients who received dialysis between 1999 and 2005 to determine the associations between baseline dementia and subsequent outcomes after dialysis. The cumulative survival rate after dialysis was calculated using the Kaplan-Meier method. Cox proportional hazards model was used to identify the risk factors for all-cause mortality. Results: A total 51,238 incident dialysis patients were examined in this study, including 867 patients with dementia. The prevalence of dementia was increasing with age. The proportional rate of dementia in elderly (?75) patients was 10 times higher than that in aged 18 44 years old of baseline. The co-morbidity with cerebrovascular disease was independently associated with dementia in dialysis population. The 1-, 5-, and 9- year cumulative survival rate were 82.1, 32.7, and 16.5% in ESRD patients with dementia, and 93.5, 62.8, and 41.6% in those without dementia (log-rank: p <0.001). ESRD patients with dementia were associated with 53% higher death risk than those without dementia (HR 1.53, 95% CI: 1.40-1.68). Conclusions: Dementia was associated with poor outcome and co-morbidities among ESRD dialysis patients.